The human pursuit of well-being a cultural approach - Brdar, Ingrid (Springer eBooks., 2011)
"This book brings together the latest research on positive psychology ... The chapters describe research and practice from diverse fields of positive psychology, covering topics such as happiness and well-being, motivation and goals, personality, academic performance and coping, measurement and interventions. The book emphasizes a cultural approach to the human pursuit of well-being. ... It presents research from a range of cultures, such as Russia, Croatia, and Egypt, in addition to ten different Western cultures. This approach helps broaden our understanding of those aspects of human experience that make life worth living in diverse cultural conditions"--From publisher's description.